(untitled) (Clinics, 2012)
OBJECTIVE: The aim of this study was to evaluate the effects of treadmill training on nociceptive sensitivity and immunoreactivity to calcitonin gene-related peptide in the dorsal horn of the spinal cord of diabetic rats. METHODS: Male Wistar rats were divided into three groups: control, diabetic and trained diabetic. Treadmill training was performed for 8 weeks. The blood glucose concentrations and body weight were evaluated 48 h after diabetes induction and every 30 days thereafter. The nociceptive sensitivity was evaluated using the tail-flick apparatus. The animals were then transcardially perfused, and the spinal cords were post-fixed, cryoprotected and sectioned in a cryostat. Immunohistochemistry for calcitonin gene-related peptide analysis was performed on the dorsal horn of the spinal cord. RESULTS: The nociceptive sensitivity analysis revealed that, compared with the control and trained diabetic animals, the latency to tail deflection on the apparatus was longer for the diabetic animals. Optical densitometry demonstrated decreased calcitonin gene-related peptide immunoreactivity in the dorsal horn of the spinal cord in diabetic animals, which was reversed by treadmill training. CONCLUSION: We concluded that treadmill training can alleviate nociceptive hypoalgesia and reverse decreased calcitonin gene-related peptide immunoreactivity in the dorsal horn of the spinal cord of diabetic animals without pharmacological treatment.